2017
DOI: 10.7186/bgsm64201701
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum systems in Southeast Asian Tertiary basins

Abstract: Productive Tertiary basins in Southeast Asia have essentially similar geodynamic developments, and share many hydrocarbon habitats and active petroleum systems. In order to facilitate understanding of the essential elements that contribute to the success of petroleum systems I have classified them into a number of groups or 'associations' according to their sedimentary facies. This facilitates use of them as valuable analogues. Five such facies associations, containing characteristic and distinct petroleum par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A deep-faulted opening, as observed on cross-section (Figure 4). It was further extent regionally in the E-W direction following a N-S compression which could be due to the extrusion of the Southeast Asia after the collision of India and resulted in N-S normal faults and subsidence in the area of the area of a Perak Valley [20] (Figure 3b). Along the N-S dip-slip fault which formed space for accumulation, the low region had deposited the Lawin conglomeratic series.…”
Section: Basin Development Of Lawin Depositsmentioning
confidence: 99%
“…A deep-faulted opening, as observed on cross-section (Figure 4). It was further extent regionally in the E-W direction following a N-S compression which could be due to the extrusion of the Southeast Asia after the collision of India and resulted in N-S normal faults and subsidence in the area of the area of a Perak Valley [20] (Figure 3b). Along the N-S dip-slip fault which formed space for accumulation, the low region had deposited the Lawin conglomeratic series.…”
Section: Basin Development Of Lawin Depositsmentioning
confidence: 99%
“…The Ciputat Subbasin was also formed and affected by the North West Java regional tectonic as well as subduction system of Southern Java. There were at least 4 stage of tectonics related to rifting process (Doust and Noble, 2017) which driven the geology and stratigraphy of the North West Java Basin, the early synrift, the late synrift, the early post rift and the late post rift. The Ciputat Sub-Basin presumed to start developed during the pre-rift tectonic event on the North West Java Basin upon the pre-Tertiary basement as described in the previous regional study shown in Figure 2.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Mineral System Definition stage is based upon geological processes. The objectives are to: (a) Define, map, and name any carbonatite or alkaline igneous-associated REE-HFSE mineral system at province scale, (b) determine the spatial and temporal distribution of the system's critical components, (c) genetically link REE-HFSE occurrences to each other and to their provenance, and (d) apply a contextual mineral system approach to evaluate the boundaries and uncertainties within which undiscovered plays and prospects may occur (modified from Reference [52]). It is a province-scale screening technique, so does not calculate any resource volumetric value, i.e., no detailed economic considerations.…”
Section: The Proposed Mineral System Definitionmentioning
confidence: 99%
“…For example, a magmatic mineralization may be used as a locus for proximal fluvial deposits, whilst lateritic deposits may indicate a location of under cover magmatic mineralization. These four facies associations incorporate the lithofacies associations concept and methodology of Reference [52], and maintain alignment with "magmatic-related", "metamorphic-related", and "basin-and surface-related" "mineralizing system families" [25]. They also parallel the four REE "mineral system associations" [42], except that we expand those authors' Regolith "Mineral-system association" [42] to Weathering, to accommodate the possibility of karst-associated mineralization in weathered carbonatite bodies.…”
mentioning
confidence: 99%